Co-digestion of cow manure, food waste and intermittent input of fat - Neves, L. (2008)
Pulses of fat were added to completely mixed reactors fed with dairy cow manure (CM) and food waste (FW). After achieving a stable performance at an organic loading rate (OLR) of 4.6± 0.1 gCOD/(Lreactor.day), an oily effluent (OE) from a canned fish processing industry was fed in the form of pulses, raising the lipids concentration up to 9, 12, 15 and 18 gCODfat/Lreactor. The highest fat concentration of 18gCODfat/Lreactor promoted a reversible inhibition in the methane production. All the other pulses had a positive effect in the methane production. From a practical point of view, this work demonstrates that controlled intermittent inputs of fat can enhance the methane production in the co-digestion of CM and FW.